Risk factors associated with progressive lacunar strokes and benefit from dual antiplatelet therapy. (18th February 2020) - Berberich, A.; Schneider, C.; Herweh, C.; Hielscher, T.; Reiff, T.; Bendszus, M.; Gumbinger, C.; Ringleb, P.
Abstract : Background and purpose: Early neurological deterioration (END) occurs in 20%–30% of patients with lacunar stroke and challenges their clinical management. This retrospective cohort study analyzed clinical and neuroimaging risk factors predicting the occurrence of END, the functional outcome after END and potential benefit from dual antiplatelet therapy (DAPT) in patients with lacunar strokes. Methods: Factors associated with END and benefit from DAPT were retrospectively analyzed in 308 patients with lacunar stroke symptoms and detected lacunar infarction by magnetic resonance imaging. END was defined by deterioration of ≥3 total National Institutes of Health Stroke Scale (NIHSS) points, ≥2 NIHSS points for limb paresis or documented deterioration within 5 days after admission. Patients were treated with DAPT according to in‐house standards. The primary efficacy end‐point for functional outcome was fulfilled if NIHSS at discharge improved after END at least to the score at admission. Results: Male gender [odds ratio (OR) 2.08; 95% confidence interval (CI) 1.09–4.00], higher age (OR = 1.65 per 10 years; 95% CI 1.18–2.31), motor paresis (OR = 18.89, 95% CI 4.66–76.57) and infarction of the internal capsule or basal ganglia (OR = 3.58, 95% CI 1.26–10.14) were associated with an increased risk for END. A larger diameter of infarction (OR = 0.85, 95% CI 0.76–0.95), more microangiopathic lesions (OR = 0.75, 95% CI 0.57–0.99) and pontine localization (OR = 0.29, 95% CI 0.12–0.65) were factors associated with unfavorable functional outcome after END occurred. Localization in the internal capsule or basal ganglia was identified as a significant predictive factor for a benefit from DAPT after END. Conclusions: Identified clinical and neuroimaging factors predicting END occurrence, functional outcome after END and potential benefit from DAPT might improve the clinical management of patients with lacunar strokes.